Right to Life and Abolition of Death Penalty - Bakhtadze, Ushangi (The European Convention on Human Rights: A Central and Eastern European Perspective, 2026)
This chapter debates the right to life versus the abolition of the death penalty in light of the European Convention of Human Rights (ECHR) and other international legal instruments. It places the right to life within the broader spectrum of fundamental human rights, weighing against a criminal justice response-capital punishment-which, worldwide, remains one of the most polemical issues.Historically, the universally practiced state-sanctioned execution was a part of human history until the death penalty was polarised in the last several centuries regarding human rights issues intermingled with ethical, philosophical, and social issues. This chapter now undertakes an in-depth review of Article 2 of the ECHR, considering what bearing it may have on state-sanctioned killings, and outlines the development of the right to life under international law. It further compares the stance of the ECHR with other key human rights instruments such as the International Covenant on Civil and Political Rights (ICCPR), underlining common approaches towards protection of life and the abolitionist trend. This chapter gives an overview of how the case law of the European Court of Human Rights (ECtHR) has set standards for an evolving understanding of human dignity through landmark decisions in cases involving the death penalty. It further focuses on the case law of the ECtHR concerning 16 Central and Eastern European countries and evaluates the impact of those judgments on national legal reforms in light of European standards. The chapter therefore concludes by integrating these findings, underlining the importance of the right to life and the leading role of the ECtHR in the universal move towards the abolition of capital punishment. Keywords: Right to Life, Death Penalty, Abolition, European Convention on Human Rights, European Court of Human Rights, Capital Punishment